Visual depictions of the Polish–German border: a quantitative analysis of visual dimension of bordering practices. - Rogowski, Łukasz; Rura, Przemysław; Rybak, Adam (Visual Studies, 2025)
We find both the quantitative approach to (de)bordering practices research and visual studies about the Polish-German border relatively underdeveloped. This paper aims at filling methodological and empirical gaps we have found in these areas. We conducted a visual content analysis of 1402 pictures of the Słubice-Frankfurt (Oder) area, sampled from Instagram, local press, and a local art project. Our coding frame enabled taking interpretations and motivations of actors into account by treating photos as manifestations of bordering practices. We used a combined approach of hypothesis-testing by common statistical methods and exploratory cluster analysis. Results include significant differences between the content of the images dependent on the depicted country and the picture source. Finally, we also critically assessed the methodological potential of the proposed method of selecting and coding photographs.